Citizen science as a tool for education: First Bioblitz in Quito, Ecuador - Páez-Vacas, Mónica (2023)
Bioblitz is a citizen global science initiative which aims to find and identify as many species of fauna and flora as possible in a specific area during a short period of time. This activity promotes the engagement of the public to learn about the biodiversity of a particular region, often in urban areas. The objective of this study was to do the first Bioblitz in Quito (Ecuador) to (1) survey the flora and fauna of Quito, specifically in the Guangüiltagua Metropolitan Park; and (2) engage citizens in such activity. This first Bioblitz, held on December 2, 2017, was organized by Universidad Tecnológica Indoamérica and Fundación Zoológica del Ecuador. The event was attended by 15 experts, 21 students, and 29 citizens, including two children under 10 years of age. Standard biological diversity assessment methods were used for amphibians, reptiles, birds, mammals, insects, aquatic macroinvertebrates, and plants. A total of 18 species of birds, two of amphibians, one reptile, 21 terrestrial invertebrates, two macroinvertebrates, one mammal, and 26 plant species were identified. This experience allowed the engagement of citizens to learn about the local biodiversity in their city.